Hospitalizations and deaths among people coinfected with HIV and HCV - Dorota Zarębska-Michaluk; Piotr Rzymski; Krzysztof Kanecki; Piotr Tyszko; Katarzyna Lewtak; Paweł Goryński; Agnieszka Genowska; Miłosz Parczewski; Robert Flisiak (Scientific Reports)
Abstract Coinfection with human immunodeficiency virus (HIV) and hepatitis C virus (HCV) remains a significant public health challenge. This retrospective, population-based study assessed the trends in hospitalization rates among patients co-infected with HCV and HIV in Poland in 2012–2022, encompassing the COVID-19 pandemic and massive influx of war refugees from Ukraine, the demographics and clinical characteristics among hospitalized patients, including in-hospital case fatality rates. Most hospitalized patients were over 40 years old (mean ± SD: 41.7 ± 8.9 years) and were men (74%). The mean annual hospitalization rate was estimated at 1.33 per 105 and was three-fold lower in the pandemic period (mean 0.51 per 105) than in the pre-pandemic era (mean 1.63 per 105). In turn, the in-hospital case-fatality rates increased during the pandemic in men (from a mean of 1.83 to 3.93) but not in women (a mean of 1.53 in both periods). There was no significant increase in hospitalization rates in 2022, during which the significant inflow of war refugees in Ukraine occurred. The epidemiological situation of people (co)infected with HIV and HCV in Poland requires further monitoring, though it did not escalate in the studied period due to the influx of war refugees from Ukraine.